What to do about rising inequality in developing countries? - Stephan Klasen (Kiel Institute for the World Economy (IfW), Poverty Reduction, Equity and Growth Network (PEGNet), 2016)
In recent years, debates about inequality have reached a renewed intensity in international policy debates. This is partly the result of much better data on the extent of inequality, where the work by Piketty on the top 1% has revealed much larger (and rising) inequality than previously known from household surveys. Similarly, work on global inequality in incomes and wealth have generated eye-catching results about the massive levels of global inequality in incomes, and even more so in wealth. Lastly, the renewed interest in inequality is also the result of rising inequality in many developing countries since the 1980s which has contributed in many places to social and political instability. In consequence, it is not surprising that the Sustainable Development Goals have included reducing inequality as a new goal. When discussing inequality, one needs to distinguish between-country, within-country, and global inequality as they are affected by very different drivers and require actions by different actors. Between-country inequality is related to differences in economic growth, and therefore reducing inequality will require poorer countries to grow faster than richer ones. This is primarily an issue of national growth strategies although the international economic environment can also play a role, as it might affect export opportunities, export prices, FDI, aid, and access to technologies. Within-country inequality is about the distribution of assets within a population, the returns that different groups receive on those assets, and to what extent the state redistributes incomes through tax and transfer systems. Global inequality, lastly, can be the result of between as well as within-country inequality and thus is affected by all of these determinants. For example, global inequality can be high because the average income of people in Sub-Saharan Africa is low compared to the rest of the world; or it can be high because the poorest in Sub-Saharan Africa are much poorer than the average incomes prevailing there. In this policy brief I will first talk briefly about global inequality and its relation to within- and between-country inequality and then focus primarily on the question what can be done to reduce within-country inequality in developing countries, and whether the international community can play a role here.
Keywords: 330